Analisis Kompetensi Guru Taman Pendidikan Al-Quran Dalam Pembelajaran Azan di Taman Pendidikan Al-Quran - Akmal Ihsan; Al Ikhlas (An-Nuha, 2022)
This research is motivated by a phenomenon of teachers who teach the call to prayer in Taman Pendidikan Al-Quran Darussalam, Lumindai Village, Barangin District, Sawahlunto City not yet meeting the qualification standards as competent teachers with the identification that teachers teach only based on personal ability and experience as participants of Musabaqah Tilawatil Quran (MTQ) and also found the fact that the teacher who taught the call to prayer at the Taman Pendidikan Al-Quran Darussalam did not meet the standards of academic qualifications, where his last education was a Sekolah Menengah Kejuruan (SMK) in Sawahlunto City. This study uses a qualitative field research method. The results of the study show that: 1) The problems faced by teachers in learning the call to prayer in Taman Pendidikan Al-Quran Darussalam, Lumindai Village, Barangin District, Sawahlunto City are divided into two, namely: a) Teacher internal factors such as the lack of teacher skills in pronouncing the call to prayer, and lack of ability of teachers in managing the potential of students; and b) external factors of teachers such as delinquency of students and lack of ability of students; 2) The teacher's way to improve the ability of students in learning the call to prayer at the Taman Pendidikan Al-Quran Darussalam in Lumindai Village is to provide reading books and increase the duration of learning; and 3) The results of the efforts of the Taman Pendidikan Al-Quran teachers in improving the ability of students in learning the call to prayer at the Taman Pendidikan Al-Quran Darussalam in Lumindai Village, Barangin District, Sawahlunto City are quite satisfying with evidence of an increase in aspects of makharijul huruf, orderly in pronouncing the call to prayer, and there were students who were selected to become Lumindai Village caravans in the sub-district MTQ event at the Friday sermon branch and the azan.